The effectiveness of the Frayer Model in teaching grammar concepts to middle school students - Shawakh, Firas Ahmad (Journal of Curriculum and Teaching Methodology, 2025)
Teaching grammar remains a significant challenge for both teachers and students, as many students struggle to grasp abstract grammatical concepts due to the reliance on rote memorization and traditional instructional methods. This study aims to investigate the impact of using the Frayer Model in teaching grammar concepts on students' academic achievement and classroom engagement at the middle school level, compared to traditional teaching methods.The study adopted a quasi-experimental design, where the Frayer Model was applied to an experimental group (26 students), while a control group (27 students) was taught using traditional methods. The impact of the model was measured using pre- and post-tests, student and teacher surveys, classroom observations, and interviews with teachers. The findings revealed that the Frayer Model significantly improved students' grammar proficiency, as the percentage of students meeting learning objectives in the experimental group increased from 30.77% to 92.31%, compared to 55.56% in the control group. Additionally, 92.45% of students in the experimental group exhibited higher classroom engagement, while 94.34% expressed a preference for the Frayer Model, citing its structured and interactive approach to learning grammar.The study concluded that the Frayer Model can be an effective instructional strategy for teaching grammar, as it enhances conceptual understanding, reduces reliance on rote memorization, and fosters active classroom participation. Based on these findings, the study recommends integrating the Frayer Model into Arabic language curricula and providing professional development programs for teachers on its implementation. Additionally, further research is encouraged to explore the model's impact on critical thinking skills and overall Arabic language learning.
Keywords: Frayer Model; Grammar Instruction; Active Learning; Classroom Engagement; Academic Achievement